Art and Entertainment as Representation of Urban Community Lifestyle in Indonesian Metropop Novels - Zulfadhli, Zulfadhli; WS, Hasanuddin; Ramadhan, Syahrul (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
As a popular novel genre, Indonesian metro pop novels are claimed to represent a cultural phenomenon of urban communities who live and settle in big cities. This cultural phenomenon is closely related to the behavior and lifestyle of the urban community. The study of urbanism is assumed to attempt to understand the patterns, attitudes, and lifestyles of urban people reflected in various aspects and activities of life. The results of this study indicate that people who live in metropolitan cities and urban communities featured in Indonesian metro pop novels are described as people who have a luxurious lifestyle, hedonic, instant, consumptive, well-established profession, and have a pragmatic approach. In addition, the lifestyle of the urban community in the metro pop novel is also reflected in the model of clothing (fashion) used, the food and beverages consumed, the language used, ways of communicating, use of various devices, forms of art and entertainment, and habit of social media.